2016
DOI: 10.7202/1035433ar
|View full text |Cite
|
Sign up to set email alerts
|

L’état de la recherche en travail social dans les communautés francophones minoritaires au Canada : une topographie thématique

Abstract: Cet article présente un inventaire thématique des écrits scientifiques sur le travail social en contexte francophone minoritaire depuis les années 1990 et cherche à stimuler une réflexion sur les rapports entre la recherche et les communautés francophones minoritaires au Canada. La description des thèmes de recherche montre un dynamisme certain de la recherche, une grande diversité d’intérêts, une prédilection pour certaines thématiques dont celles de la santé et de l’intervention auprès des femmes et des pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
4
0
3
Order By: Relevance
“…The fact that most national or PT datasets do not allow for the extraction or comparison of data based on linguistic variables further exacerbates the challenge of investigating OLMCs in a targeted fashion. 28 This obstacle is echoed by other experts in the field (Bouchard & Desmeules 23,29,39 ; Chartier et al, 29 ; Molgat & Trahan-Perreault 39 ), as well as by those consulted for the environmental scan. Bouchard & Desmeules 23 explained the lack of research on substance use in OLMCs through the following factors: the linguistic variable most often being omitted or nonstandardized across Canadian databases; an insufficient number of researchers and research infrastructures investigating this issue; and governments' interest on this topic emerging fairly recently.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that most national or PT datasets do not allow for the extraction or comparison of data based on linguistic variables further exacerbates the challenge of investigating OLMCs in a targeted fashion. 28 This obstacle is echoed by other experts in the field (Bouchard & Desmeules 23,29,39 ; Chartier et al, 29 ; Molgat & Trahan-Perreault 39 ), as well as by those consulted for the environmental scan. Bouchard & Desmeules 23 explained the lack of research on substance use in OLMCs through the following factors: the linguistic variable most often being omitted or nonstandardized across Canadian databases; an insufficient number of researchers and research infrastructures investigating this issue; and governments' interest on this topic emerging fairly recently.…”
Section: Discussionmentioning
confidence: 99%
“…To review trends in Francophone social work research in Canada, Molgat and Trahan-Perrault (2015) explored the articles in Reflets, Revue D’intervention Sociale et Communautaire from 1990 to 2014, alongside other data sources. The authors identified a strong research emphasis on health and interventions with women and immigrants, as well as salient gaps in the areas of institutional social work settings and practice with Indigenous peoples.…”
Section: Examples Of Social Work Research Using Professional Journalsmentioning
confidence: 99%
“…De plus, les mères monoparentales, les personnes seules et âgées, les personnes autochtones de même que les personnes en situation de handicap sont plus susceptibles de vivre en situation de pauvreté et ce à plus long terme (CPJ, 2017). Lorsque combinée ou articulée à d'autres facteurs de minorisation, la langue peut aussi contribuer aux écarts de revenu et au maintien, voire à la reproduction, de la précarité chez les populations francophones minoritaires au Canada, pourtant encore sous-représentées dans la littérature sur la pauvreté au Canada (Molgat & Trahan-Perreault, 2015;Coderre & Dubois, 2000;Lacroix & Nedjar, 1997;Drolet & al., 2010;Garceau & Charron, 1997).…”
Section: Pauvreté Intersectionnalité Et Subjectivitéunclassified